Pharmacy-Based Influenza Vaccination: A Study of Patient Acceptance in Romania - Chirila S; Hangan T; Gurgas L; Costache MG; Vlad MA; Nitu BF; Bittar SM; Craciun A; Condur L; Bjørklund G (Dove Medical Press, 2024)
Sergiu Chirila,1,* Tony Hangan,2,* Leonard Gurgas,1,* Monica Georgiana Costache,2,* Marinela Anisoara Vlad,3,* Bogdan-Florentin Nitu,3,* Sara Melek Bittar,4,* Aurora Craciun,5,* Laura Condur,6,* Geir Bjørklund7,* 1Department of Medical Informatics and Biostatistics, Faculty of Medicine, Ovidius University of Constanta, Constanta, Romania; 2Department of Dermatology, Faculty of Medicine, Ovidius University of Constanta, Constanta, Romania; 3Doctoral School of Medicine, Ovidius University of Constanta, Constanta, Romania; 4Department of Dermatology, County Clinical Emergency Hospital of Constanta, Constanta, Romania; 5Department of Biochemistry, Faculty of Medicine, Ovidius University of Constanta, Constanta, Romania; 6Department of Family Medicine, Faculty of Medicine, Ovidius University of Constanta, Constanta, Romania; 7Council for Nutritional and Environmental Medicine, Mo i Rana, Norway*These authors contributed equally to this workCorrespondence: Tony Hangan, University Alee nr. 1, Department of Dermatology, Faculty of Medicine, Campus B, Ovidius University of Constanta, Constanta, 900470, Romania, Email tony@medcon.roBackground: This study explores patient acceptance of influenza vaccination administered by pharmacists in Romania during the 2023 season, considering it a novel strategy to address gaps in knowledge. Pharmacy-based vaccination deviates from traditional methods, providing high-risk patients with full reimbursement and others with 50% reimbursement, allowing a choice between family doctors and pharmacies for vaccine administration.Material and Method: The survey includes 15 questions covering socio-demographic data, health information, vaccination preferences, and perceptions of pharmacy-based vaccinations.Results: Respondents showed a positive inclination toward pharmacy-based vaccination, with 68% expressing favorable sentiments, but an awareness gap exists, as only 36% were aware of pharmacy-based vaccination availability.Conclusion: Challenges include a lack of patient awareness and understanding of benefits, emphasizing the need for structured pharmacist-patient dialogues. Legal changes, a defined funding mechanism, and collaboration are crucial for successful implementation. The study provides valuable insights into patient perceptions, contributing to discussions on optimizing influenza vaccination coverage in Romania and beyond and recognizing pharmacies' potential in achieving broader vaccination goals.Keywords: pharmacy, vaccine, influenza, vaccination